Mineralogical examination of the Yamato-79 achondrites : Polymict eucrites and ureilites - Takeda, Hiroshi; Yanai, Keizo (1982)
P(論文) Mineralogical examination of the first one-third of the Yamato-79 achondrites collected by the JARE party in 1979 and 1980 seasons revealed that eight of them are polymict eucrites similar to the Antarctic polymict eucrites reported previously, and that Y-790727 is a howardite and Y-790981 is a ureilite. The following Yamato-79 eucrites show features different from the known types. Y-790122 and Y-790266 are rich in lithic clasts. A thin section of Y-790122 consists of four different clast types joined together face to face with little matrix between them. Almost one-third of Y-790266 is a medium-grained subophitic basalt with pyroxene chemical zoning trends which simulate the host pigeonite and exsolved augite pair of the ordinary eucrites such as Juvinas. Y-790007 contains abundant cumulate eucrite clasts identical to Binda in their pyroxene exsolution texture and chemistry. departmental bulletin paper